O recurso político da democracia deliberativa - Dantas, José Carlos de Castro (Universidade do Vale do Rio dos Sinos, 2017)
The basic thesis of this research takes public deliberative democracy as a theoretical paradigm and as a relevant political resource for pluralistic and complex modern contemporary democracies. It is a historical fact that, in the heterogeneous construction of Western democracy established as the most appropriate political regime, this deliberative model can now constitute a remarkable proposition of ethos and democratic praxis and, consequently, as the object of intense debates. Its defenders commonly advocate that aspects considered of common interest have to be a result of processes of rational, equitative and collective deliberation between free and equal individuals. Moreover, deliberative democracy is a conception of democratic government that prioritizes rational discussions in political life. In the Habermasian theory, in particular, contributions such as the Rawlsian liberalism, concerning preservation of subjective freedoms and public reason, and the Pettitian republicanism, related to freedom as positive non-domination, are considered within the context of rationality and discoursive principles, which ground the deliberative-procedural conception on the correlacional scope of law and politics. The context of the Porto Alegre participatory budgeting, based in the historical and local associativism and in the political will of the Popular Administration, whose metodological-discoursive procedures established that free and equal citizens qualify themselves, within the context of institutional cooperations, to debates, evaluations and decisions of public interests, was taken in this research as an exemplary model of possibility of public democratic deliberation.
Keywords: Democracia; Democracia deliberativa; Procedimentalismo; Orçamento participativo; Deliberação pública; Democracy; Deliberative democracy; Proceduralism; Participatory budgeting; Public deliberation; ACCNPQ::Ciências Humanas::Filosofia